Relationship of Exclusion From Physical Education and Bullying in Students With Specific Developmental Disorder of Scholastic Skills - Ondrej Jesina; Ladislav Baloun; Martin Kudlacek; Aneta Dolezalova; Petr Badura (Frontiers Media S.A., 2022)
Objectives: This study aimed to analyze the relationships among exclusion from PE, gender, and bullying in adolescents with specific developmental disorder of scholastic skills (SDDSS) aged 11, 13, and 15 years in Czechia.Methods: In total, the final research sample consisted of 13,953 students (49.4% boys) from the 2013/2014 Health Behaviour in School-aged Children survey. Chi-square tests and regression models stratified by presence of SDDSS diagnosis were used to assess the relationships between non-involvement in PA and bullying.Results: Students diagnosed with SDDSS (12.4% of the sample) were more likely to be excluded from physical education (PE) than students without this diagnosis. This exclusion was associated with higher odds of bullying victimization and perpetration. Our findings further showed that male gender plays a significant role for bullying perpetration for both groups (with and without SDDSS) investigated in the present study.Conclusion: Higher likelihood of aggressive behavior occurs in students who are excluded from PE, including students with SDDSS.